High Prevalence of Metabolic Syndrome and Its Related Demographic Factors in North of Iran: Results from the PERSIAN Guilan Cohort Study - Mohammadreza Naghipour; Farahnaz Joukar; Hossein-Ali Nikbakht; Soheil Hassanipour; Mehrnaz Asgharnezhad; Morteza Arab-Zozani; Fariborz Mansour-Ghanaei (International Journal of Endocrinology, 2021)
Introduction. The prevalence of metabolic syndrome has increased in recent decades around the world and is currently reaching epidemic levels as it is a major public health and clinical concern. The aim of this study was to evaluate the prevalence of metabolic syndrome and its related demographic factors in a population-based study. Methods. In this cross-sectional study, the target population consisted of 10520 individuals aged 35–70 years in Phase 1 of the Persian Guilan cohort study (Guilan site/Some’e Sara) that was conducted in 2014–2017. Demographic, anthropometric, blood pressure, and biochemical data were used in this study. The IDF definitions were used to diagnose the metabolic syndrome. Results. The prevalence of the syndrome according to IDF and ATP definition was 42.87% (95% CI: 41.92–41.81) and 40.68% (95% CI: 39.74–41.62), respectively. The prevalence of components for central obesity, high triglyceride, HDL cholesterol, blood glucose, and hypertension components was 75.8%, 43.1%, 40.6%, 39.2% and 37.9%, respectively. All demographic variables were related to the syndrome, and among them age, gender, and residence were identified as independent and strong predictive variables in the regression model. More than 92% of the population had at least one component of the syndrome. Conclusion. The results of the study show a high prevalence of metabolic syndrome risk factors. It is essential to educate healthy lifestyle behaviors and further health education in the high-risk groups identified in this study, especially the elderly, women, and rural residents.